2017
DOI: 10.1186/s12885-017-3635-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress alters the expression of cancer-related genes in the prostate

Abstract: BackgroundProstate cancer is a major contributor to mortality worldwide, and significant efforts are being undertaken to decipher specific cellular and molecular pathways underlying the disease. Chronic stress is known to suppress reproductive function and promote tumor progression in several cancer models, but our understanding of the mechanisms through which stress contributes to cancer development and progression is incomplete. We therefore examined the relationship between stress, modulation of the gonadot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 67 publications
3
19
0
1
Order By: Relevance
“…Nowadays, the understanding of the pathogenesis and biological behavior of PCa still has great limitations [8,9]. The development of PCa is a multi-factors process, in uenced by a variety of biomolecules and regulated by signaling pathways [11,12]. With the progress of the Human Genome Project, most researches on molecular and cellular pathobiology have been extensively conducted to detect the differential expression pro le of tumor genes, which is of great signi cance for exploring the molecular mechanism of PCa, and nding the molecular biomarkers in the early diagnosis and prognosis of PCa [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the understanding of the pathogenesis and biological behavior of PCa still has great limitations [8,9]. The development of PCa is a multi-factors process, in uenced by a variety of biomolecules and regulated by signaling pathways [11,12]. With the progress of the Human Genome Project, most researches on molecular and cellular pathobiology have been extensively conducted to detect the differential expression pro le of tumor genes, which is of great signi cance for exploring the molecular mechanism of PCa, and nding the molecular biomarkers in the early diagnosis and prognosis of PCa [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Although PSA test greatly improved the early-stage diagnostic rate of PCa, its bene t in decreasing the mortality of PCa remained controversial [9,10]. Like other malignancies, the malignant progress of PCa is a multi-step and multi-stage process, including inactivation of anti-oncogenes and/or activation of proto-oncogenes [11,12]. Currently, the target therapy based on cancer-related miRNAs presented a promising application, and the results of these studies showed that miRNA had a good application prospect in the diagnosis, treatment, prognosis and other aspects of cancer, to provide new ideas for the pathogenesis of PCa [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the understanding of the pathogenesis and biological behavior of PCa still has great limitations [8,9]. The development of PCa is a multi-factors process, influenced by a variety of biomolecules and regulated by signaling pathways [11,12]. With the progress of the Human Genome Project, researches on molecular level have been extensively conducted to detect the differential expression profile of tumor genes, which is of great significance for exploring the molecular mechanism of the development of PCa, and finding the molecular biomarkers in the early diagnosis and prognosis of PCa [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Although PSA test greatly improves the early-stage diagnostic rate of PCa, its benefit in decreasing the mortality of PCa remains controversial [9,10]. Like other malignancies, the malignant progress of PCa is a multi-step and multi-stage process, including inactivation of tumor suppressor genes and/or activation of proto-oncogenes [11,12]. Currently, target therapy based on tumor-related miRNAs presents a promising application, and the results of these studies showed that miRNA had a good application prospect in the diagnosis, treatment, prognosis and other aspects of cancer, to provide new ideas for the pathogenesis of PCa [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although PSA test greatly improves the early-stage diagnostic rate of PCa, its bene t in decreasing the mortality of PCa remains controversial [9,10]. Like other malignancies, the malignant progress of PCa is a multi-step and multi-stage process, including inactivation of tumor suppressor genes and/or activation of protooncogenes [11,12]. Currently, target therapy based on cancer-related miRNAs presented a promising application, and the results of these studies showed that miRNA had a good application prospect in the diagnosis, treatment, prognosis and other aspects of cancer, to provide new ideas for the pathogenesis of PCa [13,14].…”
Section: Introductionmentioning
confidence: 99%